PERSEPSI PEMAHAMAN PERANAN AUDITOR, ETIKA AUDITOR DAN INDEPENDENSI AUDITOR INTERNAL DALAM MEWUJUDKAN GOOD UNIVERSITY GOVERNANCE DENGAN GAYA KEPEMIMPINAN SEBAGAI VARIABEL MODERASI - S, Fipiariny (Universitas Muhammadiyah Palembang, 2019)
ABSTRACT The purpose of this study is to examine and analyze the influence of the role, ethics, and independence of internal auditors in implementing good university governance (GUG) with leadership style as a moderation variable. Multiple linear regression and moderation regression analysis models are used to test the hypothesis. The primary data are obtained through questionnaires that are distributed to the respondents, namely the dean and head of study program at the UniversitasBinaDarma and UniversitasMuhammadiyahPalembang. The results of this study indicate that the instruments in each variable proved to be valid and reliable. Based on the results of hypothesis testing, it can be seen that simultaneously the variable of role, ethics, and independence of internal auditors have positively and significantly effect in implementing good university governance (GUG). These results provide justification or endorsement of the theoretical truths used as the theoretical references of Stewardship Theory and Attitude and Behavioral Theory. Based on the partial test, role of auditor does not significantly affect the variable of GUG, but ethics and independence variable are found to be significant in influencing GUG. The leadership style is negative and insignificant in moderating the role of internal auditors and GUC and also the independence of internal auditor and GUC. The leadership style is found to be positive and insignificant in moderating the relationship of internal auditors’ ethics and GUC.